Against the State: Freemasonry, Patriotic Societies and the Inquisition in New Spain between the French Revolution and the Revolution of Independence - Aragón, Rogelio (2016)
In the lapse between the French Revolution and the Latin American Wars of Independence, the Inquisition actively prosecuted not only those who did not comply with Catholic orthodoxy but also those who dared to raise their voice against the Monarchy and the Government. Amongst the latter, there were many Freemasons and members of the patriotic societies shaped in a Freemasonry-like style.